(untitled) (Journal of history, 2025)
One of the most important areas of archives’ activity is acquisition. State archives are acquired by archival documents generated in the course of activities of state authorities, state institutions, organizations and enterprises, as well as documents transferred to them by non-state institutions, organizations, enterprises and citizens. From this point of view, the study of collecting problems in archival science is of particular importance. This is due to the fact that the identification and selection of historical documents, ensuring their preservation, popularization and providing public access to them are an important and responsible task. That is, the documentary complex of historical science is determined by the quality of the replenishing work in archival institutions. In addition, the problem of acquiring archives of historical and documentary heritage requires solving a number of theoretical and organizational aspects. This article provides a historiographical analysis of the works of domestic researchers on the problem of acquiring archives with documents at the present stage. The historiography of this problem has not been studied in Kazakhstan’s archival science. The study of the works of domestic researchers devoted to the analysis of the process of archival acquisition testify to the scientific interest, allowing to improve the methodological apparatus and identify new directions of archival science.